The contribution of common and rare genetic variants to variation in metabolic traits in 288,137 East Asians - Kim, Young Jin; Moon, Sanghoon; Hwang, Mi Yeong; Han, Sohee; Jang, Hye-Mi; Kong, Jinhwa; Shin, Dong Mun; Yoon, Kyungheon; Kim, Sung Min; Lee, Jong-Eun; Mahajan, Anubha; Park, Hyun-Young; et al. (Nature communications, 2022)
Metabolic traits are heritable phenotypes widely-used in assessing the risk of various diseases. We conduct a genome-wide association analysis (GWAS) of nine metabolic traits (including glycemic, lipid, liver enzyme levels) in 125,872 Korean subjects genotyped with the Korea Biobank Array. Following meta-analysis with GWAS from Biobank Japan identify 144 novel signals (MAF ≥ 1%), of which 57.0% are replicated in UK Biobank. Additionally, we discover 66 rare (MAF < 1%) variants, 94.4% of them co-incident to common loci, adding to allelic series. Although rare variants have limited contribution to overall trait variance, these lead, in carriers, substantial loss of predictive accuracy from polygenic predictions of disease risk from common variant alone. We capture groups with up to 16-fold variation in type 2 diabetes (T2D) prevalence by integration of genetic risk scores of fasting plasma glucose and T2D and the I349F rare protective variant. This study highlights the need to consider the joint contribution of both common and rare variants on inherited risk of metabolic traits and related diseases. Metabolic traits are heritable intermediate phenotypes widely used in assessing the risk of various diseases. By conducting a genome-wide meta-analysis for metabolic traits in 288,137 East Asians, the authors highlight the interplay of common and rare variants on inherited risk of metabolic traits.